the description of collaborative method used in the english teaching-learning process in the students of Sexto Grado de Educación General Básica “A” at the Unidad Educativa Militar N°6 “Combatientes de tapi “, City of Riobamba, Chimborazo Province, in the Academic Term October 2016 -March 2017”. - Hernández Cabrera, Jojaira Abigail (2017)
Collaborative method takes an essential role in the teaching and learning process. It involves groups of learners working together to solve a problem, complete a task, or create different kind of information; besides, learners are immerged socially and emotionally connecting different perspectives, defending their ideas, and performing learning activities to achieve a meaningful learning. In this project the collaborative method was researched to describe whether students of Sexto Grado de Educación Básica “A” at the Unidad Educativa Militar N°6 “Combatientes de Tapi,“ developed learning activities in which they worked together to solve a problem or answer questions about different topics sharing ideas with their classmates and building communication skills. The population was 32 students and one teacher. The ethnographic method has been used to observe the population in a direct way using different instruments such as observational guides and tally sheets in order to how the students and teacher develop collaborative method in the classroom and what collaborative learning techniques use the teacher emphasizing the importance and benefits. Analysis and interpretation of the results was achieved, in which were observed and analyzed the activities that students performed. Finally, it was determined that most of the time the teacher worked with homogeneous groups, when working with cooperative activities, a fact that prevents the achievement of learning outcomes.